2009
DOI: 10.1007/s11136-008-9434-2
|View full text |Cite
|
Sign up to set email alerts
|

Test–retest reliability of the Food Allergy Quality of Life Questionnaires (FAQLQ) for children, adolescents and adults

Abstract: Objective The self-administered Food Allergy Quality of Life Questionnaire-Child Form (FAQLQ-CF), -Teenager Form (FAQLQ-TF) and -Adult Form (FAQLQ-AF) were recently developed within EuroPrevall, a multi-centred study of food allergy in Europe. The primary aim of this study was to evaluate the test-retest reliability of the FA-QLQ-CF, -TF and -AF. Methods One hundred and one Dutch patients (31 children, 34 adolescents and 36 adults) completed the FAQLQ twice with a 10-14 day interval. The intraclass correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
46
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 29 publications
2
46
1
Order By: Relevance
“…One of the four studies also evaluated test-retest reliability of the FAQLQ-CF. The intraclass coefficient (ICC) was found to be excellent (ICC = 0.91) (10) and the same study identified the concordance correlation coefficient (CCC) as 0.907, as well as a Bland-Altman plot demonstrating that the mean differences of the test and retest were close to zero for the FAQLQ-CF (10).…”
Section: Study Selectionmentioning
confidence: 98%
See 4 more Smart Citations
“…One of the four studies also evaluated test-retest reliability of the FAQLQ-CF. The intraclass coefficient (ICC) was found to be excellent (ICC = 0.91) (10) and the same study identified the concordance correlation coefficient (CCC) as 0.907, as well as a Bland-Altman plot demonstrating that the mean differences of the test and retest were close to zero for the FAQLQ-CF (10).…”
Section: Study Selectionmentioning
confidence: 98%
“…Four papers were reviewed for the development and validation of the FA-QLQ-CF in this review (9,10,15,16).…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations